2005
DOI: 10.1161/01.hyp.0000169970.68151.17
|View full text |Cite
|
Sign up to set email alerts
|

Activation of 5-Hydroxytryptamine 1A Receptors Suppresses the Cardiovascular Response Evoked From the Dorsomedial Hypothalamic Nucleus

Abstract: Abstract-The dorsomedial hypothalamic nucleus is a key component of the central pathways subserving the cardiovascular response to psychological stress, which is believed to be an important risk factor for hypertension. Previous studies indicate that 5-hydroxytryptamine 1A receptors can modulate the cardiovascular responses associated with stress. In this study, we determined in anesthetized rats the effects of systemic or intracisternal administration of 8-hydroxy-2-(di-npropylamino)tetralin, a selective agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…In contrast, recent work from Dampney's laboratory demonstrated that systemic or intra-cisternally administered 8-OH-DPAT reduces not only tachycardia but also rises in AP and in renal sympathetic activity elicited in anesthetized rats from the dorsomedial hypothalamus (a principal ''defence area'' that mediates stress-induced cardiovascular alterations) (Horiuchi et al, 2005). Once again, the discrepancy is likely to be due to a different location in the brainstem of cardiomotor and vasomotor presympathetic neurons expressing 5-HT1A receptors.…”
Section: Anatomical Location Of Sympatho-inhibitory 5-ht1a Receptorsmentioning
confidence: 85%
“…In contrast, recent work from Dampney's laboratory demonstrated that systemic or intra-cisternally administered 8-OH-DPAT reduces not only tachycardia but also rises in AP and in renal sympathetic activity elicited in anesthetized rats from the dorsomedial hypothalamus (a principal ''defence area'' that mediates stress-induced cardiovascular alterations) (Horiuchi et al, 2005). Once again, the discrepancy is likely to be due to a different location in the brainstem of cardiomotor and vasomotor presympathetic neurons expressing 5-HT1A receptors.…”
Section: Anatomical Location Of Sympatho-inhibitory 5-ht1a Receptorsmentioning
confidence: 85%
“…Microinjection of DPAT into the region of the rRP blocks leptin-induced thermogenesis in rats (Morrison, 2004) and cold-induced cutaneous vasoconstriction in rabbits (Ootsuka and Blessing, 2006). The location of neurons containing 5-HT 1A receptors involved in the cardiovascular responses to leptin and chemical disinhibition of the dorsomedial hypothalamus has likewise been reported to be in the region of the rRP and medullary brainstem (Morrison, 2004;Horiuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Neurons in the rRP are known to express 5-HT 1A receptors (Helke et al, 1997), and studies to date have demonstrated that microinjections of DPAT into the rRP block thermogenesis induced by leptin and cutaneous vasoconstriction induced by cold (Morrison, 2004;Ootsuka and Blessing, 2006a). Likewise microinjections of DPAT into various regions of the brainstem and rRP inhibit the cardioexcitatory responses to leptin and to hypothalamic stimulation (Morrison, 2004;Horiuchi et al, 2005).…”
mentioning
confidence: 99%
“…Microinjection of BMI into the DMH has been employed in numerous studies in order to disinhibit neurons in the region (Horiuchi et al, 2004(Horiuchi et al, , 2005Da Silva et al, 2006;McDowall et al, 2006;Nakamura and Morrison, 2007), but this study represents the first in which direct evidence for neuronal activation resulting from this disinhibition has been presented. In contrast to a previous report that employed electrical stimulation and relatively high doses of kainate for study (Silveira et al, 1995), we found that the extent of the area of uniformly increased Fos expression emanating from the site of microinjection in the DMH could be delineated with reasonable clarity.…”
Section: Discussionmentioning
confidence: 99%
“…Given that projections of neurons in the DMH are predominantly ipsilateral (Thompson and Swanson, 1998), we anticipated that, as was reported previously (Silveira et al, 1995), significant lateralization of BMI-induced increases in Fos expression would be evident in areas where neuronal activation was directly dependent on neural circuitry, rather than secondary to the state of profound behavioral and "emotional" arousal so evoked. Although this dose of BMI has been employed extensively in microinjection studies targeting the DMH (Bailey and DiMicco, 2001;Samuels et al, 2002;Zaretskaia et al, 2002;Horiuchi et al, 2005;da Silva et al, 2006;de Menezes et al, 2006), the area of neuronal excitation evoked by such injections has never been delineated. Therefore, we also assessed the extent of the area of Fos expression in the vicinity of the injection site in the DMH.…”
Section: Introductionmentioning
confidence: 99%